(untitled) (Sociologisk Forskning, 2023)
The following article is based on interviews with volunteers and evacuees from the forest fires that struck the Swedish counties Gävleborg and Jämtland in the summer of 2018. The aim of the article is to explore whether and how people link their experiences of a climate-related crisis to the broader and ongoing climate crisis. The article develops the concept of crisis biography, theoretically and methodologically, to highlight how people’s experiences of crises can be understood in the context of their personal biographies. The results show that the climate crisis, and its extent in time and space, is of central importance for both people’s meaning-making of the forest fires and for their personal crisis biographies.